2016
DOI: 10.1182/blood.v128.22.210.210
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide in Hereditary Hemorrhagic Telangiectasia: Interim Results of a Phase I Study

Abstract: Background Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder characterized by telangiectasias on mucocutaneous surfaces and arteriovenous malformations in visceral organs. Most patients present with epistaxis and gastrointestinal (GI) bleeding requiring iron supplementation and blood transfusion. There is no accepted medical treatment for HHT, although several studies suggest the potential efficacy of thalidomide. However, thalidomide is not available for treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This may be particularly true for patients with significant gastrointestinal bleeding, who constituted over half the cohort in the present study, for whom there are no studies of other pharmacological interventions. Oral anti-angiogenics such as pomalidomide 36 and pazopanib 37 , 38 are additionally under investigation for treatment of HHTassociated bleeding. Should these agents demonstrate efficacy, head-to-head studies comparing them with bevacizumab will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly true for patients with significant gastrointestinal bleeding, who constituted over half the cohort in the present study, for whom there are no studies of other pharmacological interventions. Oral anti-angiogenics such as pomalidomide 36 and pazopanib 37 , 38 are additionally under investigation for treatment of HHTassociated bleeding. Should these agents demonstrate efficacy, head-to-head studies comparing them with bevacizumab will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other anti-angiogenic agents with data published for the treatment of HHT-associated bleeding include bevacizumab [15][16][17][18], thalidomide [28], and pomalidomide [29], with the largest amount of data supporting intravenous bevacizumab. Recent studies have also highlighted the anti-angiogenic potential of the antifungal itraconazole [30] and the local hemostatic capacity of intranasal fluorouracil (Efudix) [31] in HHT.…”
Section: Discussionmentioning
confidence: 99%
“…Interim results from a phase I study of pomalidomide in HHT patients have been reported in which its use was associated with reduced bleeding outcomes in a small cohort of patients. 75 Larger studies are needed to better evaluate the efficacy of this and other IMiDs in the management of bleeding in HHT.…”
Section: Clinical Trials and Future Directionsmentioning
confidence: 99%